2017
DOI: 10.9753/icce.v35.currents.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tide and Wave Directionality on Localized Tsunami-Induced Currents in Port and Harbors

Abstract: Here, we present the results of a numerical modeling study to investigate how the maxima of the tsunami-induced currents vary due to dynamic effects of tides and wave directivity. A sensitivity analyses was conducted in three harbors by coupling the tsunami with the tide signal at twelve different tide levels. We find that tsunami-tide interaction can change the maximum current speed experienced in a harbor by up to 25% for the events and harbors studied, and that this effect is highly site-specific. To evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several studies have been carried out to understand whether tide-tsunami interactions enhance/reduce tsunami elevation, flow speed, and arrival times. Based on observations and/or numerical experiments, various authors have found that tsunami inundation in rivers, inlets, harbors, and estuaries is strongly affected by tidal conditions (e.g., Kowalik et al, 2006;Kowalik and Proshutinsky, 2010;Zhang et al, 2011;Lee et al, 2015;Ayca and Lynett, 2016;Shelby et al, 2016;Tolkova, 2016;Ayca et al, 2017). Causes of tidetsunami interaction are attributed to tidally induced currents and changes in the depth altering the background conditions during the propagation of the tsunami from its source (Weisz and Winter, 2005), both effects are small in the open ocean but increase as the tsunami shoals, mainly in coastal and bathymetric particular configurations as energetic tidal channels communicating large bodies of water or coastal configuration that can induce resonance effects between large scale shallow shelfs, narrow channels, islands, etc.…”
Section: Methods and Limitationsmentioning
confidence: 99%
“…Several studies have been carried out to understand whether tide-tsunami interactions enhance/reduce tsunami elevation, flow speed, and arrival times. Based on observations and/or numerical experiments, various authors have found that tsunami inundation in rivers, inlets, harbors, and estuaries is strongly affected by tidal conditions (e.g., Kowalik et al, 2006;Kowalik and Proshutinsky, 2010;Zhang et al, 2011;Lee et al, 2015;Ayca and Lynett, 2016;Shelby et al, 2016;Tolkova, 2016;Ayca et al, 2017). Causes of tidetsunami interaction are attributed to tidally induced currents and changes in the depth altering the background conditions during the propagation of the tsunami from its source (Weisz and Winter, 2005), both effects are small in the open ocean but increase as the tsunami shoals, mainly in coastal and bathymetric particular configurations as energetic tidal channels communicating large bodies of water or coastal configuration that can induce resonance effects between large scale shallow shelfs, narrow channels, islands, etc.…”
Section: Methods and Limitationsmentioning
confidence: 99%